Working industrially or professionally? What strategies should teacher unions use to improve teacher salaries in neoliberal times?. (2nd January 2019) - Gavin, Mihajla
ABSTRACT: In recent decades, governments across Western democracies have endeavoured to inject neoliberal, market-inspired ideology into public education policy; reorganise teachers' work and conditions and undermine the collective strength of the organisations representing teachers' interests. Within this context, teachers' salaries have been subject to particular scrutiny by governments. In the Australian state of New South Wales, successive governments have utilised adversarial tactics during salary negotiations, placed legislative restrictions on wages growth and imposed limitations on union activities which have been aimed at improving teachers' salaries. This paper examines the response of the NSW Teachers' Federation to neoliberal imperatives on teacher salaries since the 1980s. To investigate this issue, this study incorporates extensive documentary analysis and in-depth interviews with NSWTF officials and members as well as senior government leaders and departmental officials. Through analysing key salaries disputes from the 1980s to the present, this paper problematises the effectiveness of industrial approaches to unionism, explores renewed strategies to achieve salary increases for teachers and contributes broadly to union renewal debates on how teacher unions can act strategically to protect and advance conditions using professional agendas.